Edukasi Deteksi Dini Stunting di TK Aisyiyah Bustanul Athfal (ABA) Kabupaten Ciamis - Sri Utami Asmarani; Ayu Endang Purwati; Dini Anggit Herdiani; Elsa Fitriana (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Malnutrition remains a major issue for infants and children under the age of five (toddlers) globally. Stunting refers to short stature or very short height for age, which is less than -2 Standard Deviations (SD) on the WHO growth curve. Stunting leads to hindrances in achieving the physical and cognitive potential of children. One of the efforts to accelerate the reduction of stunting prevalence is through early detection education for stunting in children. Objective: This community service is carried out to enhance the knowledge of parents of TK Aisyiyah Bustanul Athfal (ABA) students in Ciamis Regency about stunting and enable them to perform early detection efforts for stunting in children. Method: The implementation method involves providing early detection education on stunting through lectures using slide presentations and leaflets. Result: Parents of TK ABA students in Ciamis Regency have understood and comprehended early stunting detection. This is evident from the fact that the target audience could answer the evaluation of the presented material. Conclusion: Parents of TK ABA students in Ciamis Regency are very enthusiastic about participating in activities that involve education and discussions about stunting. This community service activity also enhances parental knowledge as an effort for early stunting detection in their children.